Improving the adoption of PBS and ABA using diffusion of innovations theory. Issue 4 (1st October 2018) - Hayward, Brent A.; Poed, Shiralee; McKay-Brown, Lisa
Abstract : Purpose: The purpose of this paper is to describe and discuss the variables which have contributed to the adoption of positive behaviour support (PBS) and applied behaviour analysis (ABA). Differences and similarities are highlighted, applications to contemporary issues in the UK and Australia are emphasised, and considerations posed for their improved adoption. Design/methodology/approach: A conceptual framework for diffusion of innovations theory is used to guide the analysis of three sets of articles, and application of the framework is guided by narrative analysis. Findings: Eight variables from the conceptual framework were identified, and the communication networks for PBS and ABA are argued to be distinct. There has been a positive change in the perception of PBS by the ABA field, but PBS has leveraged diffusion more successfully. ABA appears to have been separated from PBS in the UK while Australia is yet to fully benefit from the contributions of ABA. Those working in the fields of PBS and ABA should further collaborate for their mutual benefit. Practical implications: Greater attention to the factors which promote diffusion can assist PBS and ABA to improve their adoption. Originality/value: This is the first paper to use diffusion of innovations theory to analyse the adoption of PBS and ABA.